Wildfire : a novel - Philbrick, W. R. (W. Rodman) (Blue Sky Press, 2019)
Thirteen-year-old Sam Castine is at summer camp while his mother is in rehab, but when the camp is evacuated ahead of a fast moving wildfire, he makes the mistake of going back for his phone, and finds himself left behind, disoriented, and running for his life, together with a girl, Delphy, from a different camp--finding an old jeep keeps them going, but in the wilds of Maine, there are only logging roads and the deadly crown fire is everywhere.